Nutritional assessment among children (1-5 years of age) using various anthropometric indices in a rural area of Haryana, India - Vikas Gupta; Suraj Chawla; Debjyoti Mohapatra (Wolters Kluwer Medknow Publications, 2019)
Background: Global Nutrition Targets 2025 specified a set of six global nutrition targets, and one aim is to achieve a 40% reduction in the number of children under 5 years of age who are stunted. National data on underweight provided under National Family Health Survey-4 (NFHS-4) (2015-2016) revealed an underweight prevalence rate around 35.7% as compared to NFHS-3 where it was 42.5%, which reflects only 6.8% reduction in underweight over a decade. Methods: This cross-sectional study was conducted in the rural area of Rohtak district during October 2014 to September 2015 among children who were 1-5 years of age. The anthropometric measurement and nutritional status categorization among children were done using the WHO guidelines. Results: A total of 600 children participated in the study. Around 41.3% of the study participants had stunting as their nutritional status, while taking composite index of anthropometric failure (CIAF) for nutritional status into consideration, nearly 54.4% of the participants were undernourished. Stunting and underweight were more prevalent among girls. Conclusions: Composite anthropometric index provides the actual prevalence or proportion of undernourished children in a community, so the policies should be based on the basis of CIAF so to reduce the prevalence of undernutrition in the community more effectively.